The Effects of Trained Innate Immunity on T Cell Responses; Clinical Implications and Knowledge Gaps for Future Research - Murphy, Dearbhla M.; Mills, Kingston H. G.; Basdeo, Sharee A. (Frontiers in Immunology, 2021)
The burgeoning field of innate immune training, also called trained immunity, has given immunologists new insights into the role of innate responses in protection against infection and in modulating inflammation. Moreover, it has led to a paradigm shift in the way we think about immune memory and the interplay between innate and adaptive immune systems in conferring immunity against pathogens. Trained immunity is the term used to describe the medium-term epigenetic and metabolic reprogramming of innate immune cells in peripheral tissues or in the bone marrow stem cell niche. It is elicited by an initial challenge, followed by a significant period of rest that results in an altered response to a subsequent, unrelated challenge. Trained immunity can be associated with increased production of proinflammatory mediators, such as IL-1β, TNF and IL-6, and increased expression of markers on innate immune cells associated with antigen presentation to T cells. The microenvironment created by trained innate immune cells during the secondary challenge may have profound effects on T cell responses, such as altering the differentiation, polarisation and function of T cell subtypes, including Th17 cells. In addition, the Th1 cytokine IFN-γ plays a critical role in establishing trained immunity. In this review, we discuss the evidence that trained immunity impacts on or can be impacted by T cells. Understanding the interplay between innate immune training and how it effects adaptive immunity will give insights into how this phenomenon may affect the development or progression of disease and how it could be exploited for therapeutic interventions or to enhance vaccine efficacy.